Evaluation tool for tropical urban public space from social, cultural, and environmental diversity - Chaverri-Flores, Laura (2023)
This article expounds on an evaluation tool for public spaces in the methodological frame of the research project “Desing of the urban landscape from social, cultural, and environmental diversity of the Paseo de las Damas Complex in Costa Rica: the cases of the National, Spain, and Morazan parks” To build this tool in the national context, also applicable in other tropical latitudes, this investigation analyzed different approaches. Despite the quantity of information found, the tools tended to be destined for the social field but without considering the environment or vice versa while seeking to compare the strengths and threats of public spaces from socio-ecological diversity. The study included interdisciplinary workshops where the project researchers and other professionals participated in developing this proposal. The results were a table and an evaluation ring that contemplated four main pillars: Well-being and perception; Environment and landscape; Socioecological connectivity; and Sociability and activities. These pillars were divided into indicators with different criteria where a rubric guides the evaluator according to the sites’ characteristics. This methodology contributes to decision-making processes in interventions in public spaces.